German Language Level Improvement Through RPG Game "Deutsche Nivellierung": An Educational Approach to Interactive Learning - Kristianto, Adam Juliano; Desti Nur Aini (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2024)
The German language has an increasingly important role to play in today's global context, whether in the academic, professional or cultural fields. However, the challenges faced by German learners are often complex, especially in achieving the desired skill level. One of the main problems encountered is the lack of interactive engagement in the learning process, which can result in the inability to sustain learners' interest and motivation. In an attempt to overcome this challenge, innovative approaches need to be introduced. RPG (Role-Playing Game) games offer an engaging and interactive platform that can facilitate language learning in a fun and effective way. With the integration of German language concepts and content into RPG games, learning becomes more interesting and relevant to the learners, which in turn can increase motivation and engagement levels. The flexibility of the platform also gives students the opportunity to learn on their own schedule, while providing a variety of interactive activities that support the development of communication skills in German. The ability to track progress and assess objectively is an important component in improving the quality of learning. However, while the potential of games in language learning has been recognized, research focusing on the integration of German in RPG games is limited. Therefore, there is a significant opportunity to develop new approaches that combine RPG game elements with the German language curriculum to improve learning effectiveness. In this context, this proposal aims to develop an RPG game titled “Deutsche Nivellierung”, which is specifically designed to increase the level of comprehension and mastery of the German language. By applying an integrated educational approach, it is hoped that this game can be an effective tool in supporting interactive and fun German language learning.